Targeting of BCR-ABL1 and IRE1α induces synthetic lethality in Philadelphia-positive acute lymphoblastic leukemia. (11th September 2020) - Vieri, Margherita; Preisinger, Christian; Schemionek, Mirle; Salimi, Azam; Patterson, John B; Samali, Afshin; Brümmendorf, Tim H; Appelmann, Iris; Kharabi Masouleh, Behzad
Abstract: BCR-ABL1-positive acute lymphoblastic leukemia (ALL) cell survival is dependent on the inositol-requiring enzyme 1 alpha (IRE1α) branch of the unfolded protein response. In the current study, we have focused on exploring the efficacy of a simultaneous pharmacological inhibition of BCR-ABL1 and IRE1α in Philadelphia-positive (Ph + ) ALL using tyrosine kinase inhibitor (TKI) nilotinib and the IRE1α inhibitor MKC-8866. The combination of 0.5 µM nilotinib and 30 µM MKC-8866 in Ph + ALL cell lines led to a synergistic effect on cell viability. To mimic this dual inhibition on a genetic level, pre-B-cells from conditional Xbp1 +/fl mice were transduced with a BCR-ABL1 construct and with either tamoxifen-inducible cre or empty vector. Cells showed a significant sensitization to the effect of TKIs after the induction of the heterozygous deletion. Finally, we performed a phosphoproteomic analysis on Ph + ALL cell lines treated with the combination of nilotinib and MKC-8866 to identify potential targets involved in their synergistic effect. An enhanced activation of p38 mitogen-activated protein kinase α (p38α MAPK) was identified. In line with this findings, p38 MAPK and, another important endoplasmic reticulum-stress-related kinase, c-Jun N-terminal kinase (JNK) were found to mediate the potentiated cytotoxic effect induced by the combination of MKC-8866 and nilotinib since the targeting of p38 MAPK with its specific inhibitor BIRB-796 or JNK with JNK-in-8 hindered the synergistic effect observed upon treatment with nilotinib and MKC-8866. In conclusion, the identified combined action of nilotinib and MKC-8866 might represent a successful therapeutic strategy in high-risk Ph + ALL. Abstract : BCR-ABL1 inhibitor nilotinib and inositol-requiring enzyme 1 alpha inhibitor MKC-8866 are synergistic in Philadelphia-positive acute lymphoblastic leukemia and the activation of p38 mitogen-activated protein kinase/c-Jun N-terminal kinase pathways is the main mechanism at the basis of the synergism observed.